Taste evaluation of Chinese oolong tea “Baiyaqilan” based on physiological signals and multivariate statistics - YANG Bo-kai; SHEN Li-juan; YANG Jing-min (Shipin yu jixie)
Objective: Investigate young people's taste preference for white bud kiran tea and design tea drinks accordingly. Methods: Design a combination of electroencephalogram （EEG）, electrodermal activity （EDA）, heart rate variability （HRV） multivariate statistical analysis and sensory evaluation to allow 24 subjects （12 of each gender） to evaluate the taste preference of seven batches of white bud kiran tea of different grams and brewing lengths. Results: the mean values of power spectral density, HRV and EDA of EEG can predict the taste preference of the subjects more accurately, and the mean values are negatively correlated with the liking level. A two-way analysis of variance shows that HRV and EDA are not affected by gender differences between subjects and the subject tea sample. Conclusion: Most of the subjects preferred the taste of 10 grams of white bud kiran tea brewed for 10 seconds.